2018
DOI: 10.1111/evj.12954
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in equine veterinary science

Abstract: MicroRNAs are small noncoding RNAs that play a pivotal role in diverse cellular processes through post-transcriptional regulation of gene expression. The dysregulation of specific microRNAs is associated with disease development and progression. In this review, we summarise how microRNAs modulate gene expression, and explain microRNA nomenclature. We discuss the potential applications of microRNAs in equine disease diagnosis and treatment, in the context of the sum of current knowledge about microRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…Physiological and pathological roles of miRNA in animal diseases has been the subject of intensive research for only a few years. MicroRNAs are involved in a broad spectrum animal disease, among which the following ones should be mentioned above all: cancer, metabolic and infection diseases and immune defense [76,77] (Table 2). Cancer.…”
Section: Micrornas As Potential Biomarkers For Veterinary Researchmentioning
confidence: 99%
“…Physiological and pathological roles of miRNA in animal diseases has been the subject of intensive research for only a few years. MicroRNAs are involved in a broad spectrum animal disease, among which the following ones should be mentioned above all: cancer, metabolic and infection diseases and immune defense [76,77] (Table 2). Cancer.…”
Section: Micrornas As Potential Biomarkers For Veterinary Researchmentioning
confidence: 99%
“…Some miRNAs can be excreted in the plasma, packed in exosomes, or bound to proteins. 23 Similar to the measurement of gene expression, the measurement of the cell-free miRNAs expression in the plasma seems suitable for doping control, especially because the starting material, plasma, is easy to collect and store. In humans, circulating miRNAs were demonstrated as potential doping markers particularly for erythropoietin (EPO), 24 AAS, 25 GH 26 administrations as well as for blood doping.…”
Section: Introductionmentioning
confidence: 99%
“…The miRNAs are small non‐coding RNAs that regulate gene expression. Some miRNAs can be excreted in the plasma, packed in exosomes, or bound to proteins 23 . Similar to the measurement of gene expression, the measurement of the cell‐free miRNAs expression in the plasma seems suitable for doping control, especially because the starting material, plasma, is easy to collect and store.…”
Section: Introductionmentioning
confidence: 99%
“…By targeting the three prime untranslated region (3′-UTR) region of protein-coding genes, miRNAs affect the expression of target genes, thereby influencing cell growth, proliferation, differentiation, apoptosis, and other biological behaviors. [9,10] Numerous studies have demonstrated that miRNAs are implicated in the pathogenesis of ALI. [11] Reportedly, miRNA-1246 suppresses ALI-induced inflammation and apoptosis via the NF-κB and Wnt/β-catenin pathways.…”
Section: Introductionmentioning
confidence: 99%